ANALISIS 7 UNSUR KEBUDAYAAN MASYARAKAT KECAMATAN CIGALONTANG KABUPATEN TASIKMALAYA - Krisma Jayanti; Aini Loita; Helda Safaat (Magelaran: Jurnal Pendidikan Seni, 2019)
This article is the result of a qualitative descriptive study focused on the study of seven elements of culture including systems of technology, livelihoods, social systems and social organizations, languages, arts, education, and religious systems. Most of the residents of Cigalontang speak Sundanese and are Muslim. Most people who work as farmers are still very traditional, have diverse cultural customs including jaipongan, pencak silat, rudat, calung, ronggeng, tambourine, dog dogs, and are cut down by gebes. In addition, there are also traditional hereditary practices that are usually carried out by the community, namely randomizing those who want to get married and thanksgiving for the harvest if they are going to harvest by burning incense.